Interface manipulation of CO2–philic composite membranes containing designed UiO-66 derivatives towards highly efficient CO2 capture - Xu, Jiang; Li, Songwei; He, Shanshan; Bai, Yongping; Shao, Lu (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Both material choice and filler/organic interface are crucial in mixed matrix membranes (MMMs) for sub-nano-size gas separations and yet, the interface–performance relationship is still a subject of intense debate due to challenging interfacial detection. Herein, two UiO-66-type MOFs (amino-functionalized UiO-66-NH2 and isopropenyl-functionalized UiO-66-MA) are incorporated in cross-linked CO2–philic polyethylene oxide (PEO) matrix based on judicious material screening for CO2 capture. The reactive material UiO-66-MA is stitched together with methacrylate-capped PEO in situ during UV-induced copolymerization to generate highly efficient gas transport passages with conceivably good interfaces. Poor interface is observed by substituting UiO-66-MA with non-reactive UiO-66-NH2 in MPCM (MOF/polymer composite membrane). The interfacial conditions of CO2–philic MPCMs are carefully assessed via advanced physicochemical characterizations for clarifying the correlation between interface and separation performance. The reactive material UiO-66-MA containing MPCM with good interface demonstrates higher gas permeability (up to 1450 barrers) with similar selectivity (up to 45.8 for CO2/N2) when compared to non-reactive UiO-66-NH2 containing MPCM. The mixed gas test also shows high CO2 permeability of 1439 barrer and CO2/N2 selectivity of 37.6 in our MPCM. We also observe unexpected suppressed plasticization/swelling behaviour in UiO-66-MA containing MPCM and enhanced plasticization in UiO-66-NH2 containing MPCM through analysis of gas separation performance in the range of 1–10 atm, which might be utilized as a potential interface assessment tool for nanocomposites. Moreover, the performances of our CO2–philic MPCMs can be optimized further to surpass the (2008) Robeson Upper Bound for highly efficient sustainable CO2 capture.